INVESTIGATION OF THE COUPLING PROPERTIES OF THE ELECTRIC TRAINS ON FOUR UNIAXIAL TRUCKS - Savoskyn, O. M.; Serdobintsev, Ye. V.; Krushev, S. D.; Zvantsev, P. M. (Science and Transport Progress, 2005)
In given article are considered processes, appearing in tractive электроприводе motor coach электропоезда on four одноосных pushcart at failure of the traction. Also happen to the frequencies of the fluctuations this drive element both before, and after failure of the traction.